Literary Translation Into English of Peter Khuzangai's Poem "The Poet" - Svetlana N. Vasilyeva; Anna V. Gordeeva (Publishing house "Sreda", 2022)
The purpose of the article is to present a literary translation into English of P. Khuzangay's poem «A Poet» and to make a comprehensive analysis of it. The object of the study is the text of P. Khuzangay's poem «A Poet» and the literary translation of S. N. Vasilyeva «A Poet». The novelty of the work lies in the fact that a literary translation and a comprehensive analysis of this poem were carried out for the first time. Based on the methods of analytical reading, theoretical analysis of literature, search, contextual analysis, comparative analysis, the language of the work (morphology, syntax, vocabulary, style) is considered and the relationship between the ideological and artistic conception of the poem with its linguistic features is revealed. The methods used in the process of literary translation made it possible to preserve the idea of the poem, the features of the composition and to select the appropriate means of artistic expression. In the work of P. Khuzangay, the philosophical problem of the poet's destiny and his work is touched upon. The composition of the poem is three-part, the size is a three-foot trochee with cross-rhyming throughout the entire poem, the intonation is narrative. The translation was made using the technique of rhetorical exclamation. The temporal organization is interesting: throughout the poem, verbs are transmitted in the present tense. The translation is dominated by complex sentences. As a rule, a stanza corresponds to one sentence. Alliteration and assonance are used to enhance sound expressiveness and achieve speech imagery.